GAMBARAN PERSEPSI DAN KESIAPAN MAHASISWA TERHADAP IMPLEMENTASI IPE (INTERPROFESSIONAL EDUCATION) DI STIKES SURYA GLOBAL YOGYAKARTA - Rasmita, Dina (Universitas Prima Indonesia, 2018)
Interprofessional Education (IPE) is a collaborative practice with two or more health professions that each studying the role of each health profession to improve collaboration and quality of health care. The objective of study was getting a general overview on students' perception and readiness for IPE at the STIKes Surya Global Yogyakarta. The methode of study was descriptive explorative with cross sectional design and quantitative as well as qualitative approaches. Samples consisted of 30 undergraduate students, nursing, public health, and pharmacy that they selected purposive sampling method. Quantitative data were obtained through questionnaire of interdisclipinary Education Perception Scale (IEPS) and Readiness Interprofessional Learning Scale (RIPLS). Qualitative data gathered through focus group discussion. The result of study was perception about IPE mainly belonged to good (60%). Readiness for IPE mainly belonged to good (83,3%). Perception and readiness for IPE of undergraduate students at the STIKes Surya Global Yogyakarta mainly belonged to good category.